Kecerdasan Naturalistik sebagai Basis Pembentukan Karakter Religius-Ekologis dalam Manajemen Pendidikan Islam - Lelah Nurjamilah; Jaenal Mutaqin; Akhmad Roziqin; Ulfah Ulfah (CV. Alim's Publishing, 2026)
The accelerating global ecological crisis, manifested in deforestation, biodiversity collapse, and extreme climate change, fundamentally reflects a deep-rooted moral and spiritual deterioration within modern humanity. Islamic Religious Education (PAI) holds a unique strategic position to address this crisis by systematically integrating naturalistic intelligence, the eighth dimension of Howard Gardner's Multiple Intelligences theory, into the character formation process of students. This qualitative library research employs content analysis and conceptual analysis techniques applied to relevant primary and secondary academic sources published between 2019 and 2026. The study pursues three objectives: (1) to examine the conceptual and theological foundations of naturalistic intelligence within the Islamic educational framework; (2) to identify the reciprocal relationship patterns between naturalistic intelligence and the formation of religious-ecological character in students; and (3) to formulate integrative Islamic education management strategies for optimizing naturalistic intelligence. Findings reveal that naturalistic intelligence possesses robust theological grounding in Islamic tradition, anchored in the concepts of tafakkur, ayat kauniyah, khalifatullah fil ardh, and scientia sacra, none of which are peripheral but rather central to the Islamic worldview. The relationship between naturalistic intelligence and religious-ecological character is bidirectional and mutually reinforcing, operating through three sequential pathways: from naturalistic intelligence to theological consciousness, from theological consciousness to intrinsic ecological motivation, and from intrinsic motivation to consistent religious-ecological behavior. Islamic education management can optimize naturalistic intelligence development through four strategic pillars: reconstruction of the PAI curriculum based on ayat kauniyah, development of innovative eco-theological pedagogy, construction of an eco-conscious school culture, and strengthening of school-family-community partnerships. This study advances the concept of